The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s13104-020-05368-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of climatic and geographical factors on breast cancer in Iran

Abstract: Objective By studying the effect of environmental factors on health, it is clear that geographical, climatic and environmental factors have a significant impact on human health. This study, based on the data of the patients with breast cancer in Iran since 2010 to 2014 and using the statistical methods has determined the effect of geographical features of Iran (solar radiation status, radiation angle) on the frequency and distribution of this disease. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…In western countries, breast cancer is mainly observed in ages over 50, while based on some studies conducted in Iran in 2018, the number of breast cancer patients aged between 40 and 49 is higher than in other age groups. In addition, the number of younger patients in Iran is higher than that of the Western countries ( 7 ). Social support as one of the most emotional coping mechanisms is recognized as the greatest and most powerful coping force for patients to cope with cancer and its stressful conditions successfully and effectively ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 97%
“…In western countries, breast cancer is mainly observed in ages over 50, while based on some studies conducted in Iran in 2018, the number of breast cancer patients aged between 40 and 49 is higher than in other age groups. In addition, the number of younger patients in Iran is higher than that of the Western countries ( 7 ). Social support as one of the most emotional coping mechanisms is recognized as the greatest and most powerful coping force for patients to cope with cancer and its stressful conditions successfully and effectively ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 97%
“…This may be as a result of differences in climate, environmental factors, culture, dietary, and other social patterns that exist between the two regions. These factors are known to have influence on the incidence of breast cancer generally [29]. The proportions of AYAs with breast cancer in the northern and southern regions were similar at 32.2% and 31.5%, respectively (Table 4).…”
mentioning
confidence: 93%
“…Previous evidence suggested that high-altitude populations were at higher risk for breast cancer, compared with lowaltitude populations. And mounting evidence presented various differences of gene expression during breast cancer process between high-and low-altitude populations (12). Compared to low-altitude regions, the most obvious distinctions of high-altitude regions are intense ultraviolet radiation, hypoxia, and low pressure.…”
Section: Discussionmentioning
confidence: 99%